2010
DOI: 10.1248/bpb.33.876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sebum and Ointment Rubbing on the Skin Permeation of Triamcinolone Acetonide from White Petrolatum Ointment

Abstract: It is very important to clarify the partition and diffusion of drugs into and through the skin barrier for effective therapy when using topical drug formulations. Several studies have already been carried out on the release and skin permeation of drugs from topical formulations such as ointments and creams. [1][2][3][4] We have studied the effect of sebum or relative skin lipids on the release and skin permeation of drugs from topical formulations. When a pressure sensitive adhesive (PSA) patch containing lido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Then, 1.0% CP or PS cream (Ca. 300 mg) was placed in a disc-shaped cell cap [6], and the cell cap was applied to the epidermal side of the hydrated dorsal skin, which was placed in a diffusion cell with an effective permeation area of 0.95 cm 2 , surrounded by a water jacket connected to a water bath at 32°C, while 3.0 ml of pH 7.4 PBS or 0.54 µmol/ ml DFP/pH 7.4 PBS was applied to the dermal side [18]. The receiver compartment was agitated using a magnetic stirrer and a stirrer bar.…”
Section: In Vitro Skin Permeation Experiments Using Clobetasol Propiomentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 1.0% CP or PS cream (Ca. 300 mg) was placed in a disc-shaped cell cap [6], and the cell cap was applied to the epidermal side of the hydrated dorsal skin, which was placed in a diffusion cell with an effective permeation area of 0.95 cm 2 , surrounded by a water jacket connected to a water bath at 32°C, while 3.0 ml of pH 7.4 PBS or 0.54 µmol/ ml DFP/pH 7.4 PBS was applied to the dermal side [18]. The receiver compartment was agitated using a magnetic stirrer and a stirrer bar.…”
Section: In Vitro Skin Permeation Experiments Using Clobetasol Propiomentioning
confidence: 99%
“…before application of the cream to this site, the skin color was measured using a Chroma Meter (CR-400, Konica Minolta Sensing, Inc., Tokyo, Japan). Then, 0.005, 0.01, 0.1, or 1.0% CP or PS cream (Ca 100 mg) was rubbed into the application site at a pressure of 1.87-3.12 N/cm 2 using a rubber-covered forefinger for 30 s [6]. Similarly, drug-free hydrophilic cream was also applied to some sites using the same method as the control.…”
Section: Measurement Of the Vasoconstrictive Effects Of Topically Appmentioning
confidence: 99%
“…Since the API concentration in solvent is known to influence its skin permeation, 27,28 the solvent concentration in the ointments is an important factor. The solvent concentrations in TCR ointments that were detected using GC-MS are shown in Table IV.…”
Section: Resultsmentioning
confidence: 99%
“…Okuda and Yoshiike reported that rubbing the skin may worsen skin functions 9 . Furthermore, skin friction, massaging, and rubbing are related to stratum corneum functions 13‐16 and often increase the chemical penetration rate of the skin 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, skin friction, massaging, and rubbing are related to stratum corneum functions [13][14][15][16] and often increase the chemical penetration rate of the skin. 17,18 Many people recognize that rubbing their skin may worsen their skin conditions. In this evaluation, all subjects considered that they did not rub their skin hard during the cleansing and felt that their own cleanser did not worsen their skin symptoms (data not shown).…”
Section: Discussionmentioning
confidence: 99%